2022
DOI: 10.36456/wahana.v74i2.6269
|View full text |Cite
|
Sign up to set email alerts
|

Rancang Bangun Penyusunan Laporan Keuangan Berbasis Excel Pada PT Raksaka Teknologi Indonesia

Abstract: The object of this research is PT Raksaka Teknologi Indonesia, a company engaged in the IT sector, having its address at Jalan girlfriend No. 2A, Ketabang, Jl. Gayungsari Timur No.16 (MGI-2) Genteeng District, Surabaya. The purpose of this study was to determine the existing transaction recording system at PT Raksaka Teknologi Indonesia and to design the preparation of the financial statements of PT Raksaka Teknologi Indonesia using Microsoft Excel for Accounting. The research design used is a system design me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Even literacy activities in Papua are the lowest compared to all provinces in Indonesia [11]. From the results of research conducted by WVI (Wahana Visi Indonesia) in 2022 [12] in 4 districts of Papua, namely; Sentani, Biak, Pegunungan Tengah, and Asmat, it was found that on average only 36.1% of grade 3 elementary school children have reading skills with comprehension [13] Facts in the field, there are still many school children who do not have basic reading, writing and counting skills [14] In 2016, Puspendik of the Ministry of Education and Culture conducted reading, mathematics, and science skills tests for grade IV elementary school students through the Indonesian National Assessment Program (INAP). The results of the reading skills test showed that 46.83% were in the less category, 47.11% in the sufficient category, and only 6.06% in the good category [15].…”
Section: Introductionmentioning
confidence: 99%
“…Even literacy activities in Papua are the lowest compared to all provinces in Indonesia [11]. From the results of research conducted by WVI (Wahana Visi Indonesia) in 2022 [12] in 4 districts of Papua, namely; Sentani, Biak, Pegunungan Tengah, and Asmat, it was found that on average only 36.1% of grade 3 elementary school children have reading skills with comprehension [13] Facts in the field, there are still many school children who do not have basic reading, writing and counting skills [14] In 2016, Puspendik of the Ministry of Education and Culture conducted reading, mathematics, and science skills tests for grade IV elementary school students through the Indonesian National Assessment Program (INAP). The results of the reading skills test showed that 46.83% were in the less category, 47.11% in the sufficient category, and only 6.06% in the good category [15].…”
Section: Introductionmentioning
confidence: 99%